2010
DOI: 10.1103/physreva.81.023416
|View full text |Cite
|
Sign up to set email alerts
|

Level-crossing absorption with narrow spectral width in Rb vapor with buffer gas

Abstract: We present the transformation in the Hanle configuration of the transmission that results from coherent population trapping (CPT) into the level-crossing absorption (LCA) that results from the single-photon optical pumping in the 87 Rb D 1 line of a Rb vapor cell with a Ne buffer gas when the polarization of the laser field is changed from linear to circular. The LCA spectrum, with a narrow spectral width of 2.4 mG (1.7 kHz), was observed in the F g → F e F g transition with the circularly polarized laser. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…A comparison with the experimental results presented in Ref. [37] showed that the magnitude of the transverse magnetic field was approximately 1 mG.…”
Section: -3supporting
confidence: 52%
See 3 more Smart Citations
“…A comparison with the experimental results presented in Ref. [37] showed that the magnitude of the transverse magnetic field was approximately 1 mG.…”
Section: -3supporting
confidence: 52%
“…Therefore, information obtained at the condition of the elliptic polarization may be used to determine the angle between the x axis and the direction of the transverse magnetic field. Figure 6(b) shows the experimental results presented in a previous report [37]. A rough comparison of Figs.…”
Section: -3mentioning
confidence: 78%
See 2 more Smart Citations
“…We further note that for finite B-field the role of QI is negligible and OP drives the direction dependent absorption. Even in absence of QI such direction dependent OP response has been associated with EIT or EIA [30][31][32].…”
Section: Liamentioning
confidence: 99%